Platelet Volume Parameters as Predictors of Valvular Thrombosis Risk in Patients with Aortic and Mitral Valve Replacement - Boshra Pourbashash MD; Seyed Parsa Eftekhar MD; Pooria Ahmadi MD; Arash Jalali PhD; Ali Hosseinsabet MD; Reza Mohseni Badalabadi MD (Clinical and Applied Thrombosis/Hemostasis)
Percutaneous valve implantation or surgical replacement with mechanical or biological valves are standard therapies for severe valvular heart diseases. Prosthetic valve thrombosis, though rare, is a serious complication, particularly with mechanical prostheses. This study aimed to investigate the predictive value of platelet volume parameters, including mean platelet volume (MPV), platelet distribution width (PDW), and platelet-large cell ratio (P-LCR), for valvular thrombosis risk in patients undergoing valve replacement therapy. A retrospective cross-sectional study was conducted from May 2002 to May 2020, involving 108 patients with a history of mitral or aortic valve replacement and valvular thrombosis, and 216 controls with a history of valve surgery without valvular malfunction. PDW was significantly associated with an increased risk of thrombosis after adjusting for confounders, while MPV showed a clinical difference but did not reach statistical significance. P-LCR did not exhibit a significant association. These findings suggest PDW as a potential predictor of valvular thrombosis in such patients. The ease of measuring platelet volume parameters suggests their utility in routine hematological analysis for identifying patients at higher risk of valvular thrombosis post-replacement surgery. Further studies are warranted to validate these findings and explore additional laboratory markers, such inflammatory markers, for thrombotic risk assessment in this population.